Kwang'wen in Lushoto, Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Photos taken at the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) research benchmark site in Lushoto, Tanzania.